Is Marriage Age Restriction Un-Islamic? (Comparative Study of Indonesia and Pakistan with Gender Perspective) - Retnowulandari, Wahyuni; Indrasti, Maya; Fitriliani, Yulia (KnE Social Sciences, 2024)
Like a recent epidemic, child marriages are prevalent not only in Indonesia but also in Pakistan. Even though both countries have ratified CEDAW and have laws and regulations governing the age of marriage. However, the BPS data (2020-2022) shows that the number of underage marriages are still high in several regions, with up to 34,000 applicants for marriage dispensation in 2022 in Indonesia. Likewise, the phenomenon also occurs in Pakistan, as its Human Rights Commission in Lahore in 2022 stated that at least 99 cases of child marriage were reported to them. Why is it difficult for the two countries to suppress the number of child marriages? Is it because the age limit for marriage is not Islamic? And what are the countermeasures from a gender perspective? Using the comparative method of laws in Indonesia and Pakistan from secondary sources, it can be concluded that these two countries are predominantly Muslim. Although the legal systems used in both countries are plural, where the law of marriage is still strong in Islamic law, and regarding the application of the marriage age, both the countries have attempted to have an age limit. Even though in the Islamic conception there is no age limit for marriage and only aqil and baliq are required, which according to most scholars stipulate that the age of aqil baliq is not the same as one another. This shows that the age limit for marriage is very Islamic because it is for the benefit of the child. Apart from that social culture poverty and promiscuity also contributed to the increase in the number of underage marriages. Therefore, it is necessary to fulfill the legal awareness of all parties, especially law enforcement in overcoming the negative impact on children’s rights (especially girls). Keywords: underage marriage, Islamic concept, children’s rights, gender perspective, comparative law